Good job – bad job. Are personal assistance services for people with disabilities doomed to precarious employment and working conditions? - Giermanowska, Ewa (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The article is part of a discussion on building professional roles in the care sector, illustrating it with the example of personal assistant services for people with disabilities. It refers to interdisciplinary research and a multidimensional approach to work quality, conceptualization of the concepts of „good job” and „bad job” as well as sociological concepts and research on the precarization of work. Personal assistance services are becoming an increasingly expected and available service for people with disabilities. The adoption of the Convention on the Rights of Persons with Disabilities (2006) by the United Nations General Assembly accelerated the processes of implementing the service in individual countries and developing its standards. The specificity of a service contract and the expectations of a person with a disability and his or her assistant often go beyond traditional service and employment relationships, becoming a source of change and sometimes violation of the terms of the contract. State administrations try to regulate personal assistance services and the employment and working conditions of assistants. Based on the analysis of documents and research results on personal assistance services in Poland and Norway, conducted in 2020-2022, the author presents similarities and differences regarding the professional position of assistants in both countries. She also refers to the results of other national and international research projects.